(untitled) (American Journal of Arts and Human Science, 2023)
Diplomacy as a means of communication between states has been and still is the most effective way to achieve the goals set before a state. Special emphasis and importance is given to preventive diplomacy, which day by day occupies an increasingly important place in resolving disputes and preventing conflicts. The legal basis for the application of prevention in the process of prevention or escalation of conflicts is found in the Charter of the United Nations. The overall work of the UN is based on prevention and it promotes mechanisms and instruments for peacekeeping. Establishing a preventive mission is far more cost-effective than taking other post-conflict measures. The real importance of prevention is seen in this segment. In the former parts of the former Yugoslavia that gained independence, preventive diplomacy played a very important role. In the Republic of Bosnia and Herzegovina, in the Republic of Kosovo, in the Republic of Macedonia, there was a need for a preventive mission on their territories. The establishment of the missions of the United Nations, the OSCE, and later of the European Union and the United States of America proved to be a good example of preventing the spread of the conflict and can serve as a model for future prevention missions based on the Balkan experience. The benefits of a preventive mission can be great, both for the host country and for neighboring countries.